The Role of Islamic Values in Strengthening Effects of Kaizen, Employee Loyalty and Accounting Information System to Cost Reduction - Azwar Anwar; Muslimin H. Kara; Wahyuddin Abdullah; Murtiadi Awaluddin (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to empirically test several determinant factors that effect of achieving cost reduction strategies and how Islamic values may strengthening these factors. The companies which is developing cost reduction strategies must have a competitive advantage based on different capabilities with unique characteristics in core values. Islamic values are core values as part of the organizational culture that is internalized in the Kalla Group company (a business group in Indonesia). This study uses quantitative methods with SEM PLS analysis tools. Data collection through electronic surveys circulated at all managerial levels of Kalla Group companies. Samples were taken randomly and obtained as many as 100 respondents fullfill criteria. Based on empirical testing, the results show that all the determinants of cost reduction, Kaizen, Employee Loyalty and Effectiveness of Accounting Information Systems (AIS), have a significant positive effect, and the effect increases with the presence of Islamic Values as a moderating variable.